Agronomic Performance of Grain Sorghum (Sorghum bicolor (L.) Moench) Cultivars under Intensive Fish Farm Effluent Irrigation - Ildikó Kolozsvári; Ágnes Kun; Mihály Jancsó; Andrea Palágyi; Csaba Bozán; Csaba Gyuricza (Agronomy, 2022)
The growing global water shortage is an increasing challenge for the agricultural sector, which aims to produce sufficient quantity and quality of food and animal feed. In our study, effluent water from an intensive African catfish farm was irrigated on grain sorghum plants in four consecutive years. In our study the effects of the effluent on the N, P, K, Na content of the seeds, on the phenological parameters (plant height, relative chlorophyll content), the green mass, and on the grain yield of three varieties (‘Alföldi 1’, ‘Farmsugro 180’ and ‘GK Emese’) were investigated. Five treatments (Körös River (K) water and effluent (E) water: 30 and 45 mm weekly irrigation water dose; non-irrigated control) were applied with micro-spray irrigation. Compared to non-irrigated plants, effluent water did not negatively affect the N, P, K and Na contents of the grain crop. In terms of phenological parameters, the quality of the irrigation water (150–230 cm) had no negative effect on any of the measured parameters compared to the control (133–187 cm) values. In terms of biomass in 2020, grain yields were 89–109 g/plant with variety Alföldi 1, 64–91 g/plant with variety Farmsugro 180, and 86–110 g/plant with GK Emese.